Metastable Phase Cu with Optimized Local Electronic State for Efficient Electrocatalytic Production of Ammonia from Nitrate. (28th November 2022) - Wen, Weidong; Yan, Ping; Sun, Wanping; Zhou, Yitong; Yu, Xin‐Yao
Abstract: Electrocatalytic nitrate (NO3 − ) reduction reaction (NITRR) is an inspiring route for ammonia (NH3 ) synthesis at ambient condition. The metallic Cu‐based material with low cost and high activity is one of the most promising electrocatalysts for NITRR. However, due to the weaker atomic H * ‐providing capacity, the produced intermediate—nitrite tends to accumulate on its surface, leading to unsatisfactory NH3 selectivity and Faradic efficiency (FE). Herein, a novel and facile O2 /Ar plasma oxidation and subsequent electro‐reduction strategy is developed to synthesize a kind of metastable phase Cu. Excitingly, the metastable phase Cu demonstrates superior NITRR performance to conventional phase Cu with high NH4 + selectivity (97.8%) and FE (99.8%). Density function theory (DFT) calculations reveal that the upshift of the d ‐band center to near the Fermi level in metastable phase Cu contributes to the enhanced activity, while the relatively strong adsorption of H * facilitates the conversion from NO2 * /NO * to NOOH * /NOH * and thus ensures high selectivity and FE. Furthermore, when evaluated as cathode material in Zn‐NO3 − battery, high power density (7.56 mW cm −2 ) and NH4 + yield (76 µmol h −1  cm −2 ) are achieved by the metastable phase Cu‐based battery. Abstract : Metastable phase Cu is synthesized by a novel O2 /Ar plasma oxidation and subsequent electro‐reduction strategy. Due to the unique electronic structure, the metastable phase Cu exhibits superior electrocatalytic nitrate reduction performance to conventional phase Cu for ammonia synthesis. Specifically, the metastable phase Cu can significantly promote the coupling of NO2 − with active H atoms, thus improving the performance of NH3 synthesis.